GROWTH RESPONSE AND RESULTS ON SABRANG ONION (Eleutherine americana Merr) AGAINST OF GRANTING SOLID ORGANIC FERTILIZER ON PEAT - Adrianus Sepoel; MAULIDI MAULIDI; Agus Hariyanti (Fakultas Pertanian Universitas Tanjungpura, 2018)
ABSTRAK This study aims to determine the growth and yield response of the best Sabrang on the provision of Organic Solid Fertilizer on peat. The research was carried out on Jl Reformasi GG. Matematika Pontianak Tenggara West Kalimantan, in 7 November 2017 to 8 January 2018. The research method used was Completely Randomized Design consist of 5 treatments namely (p1): 10 g, (p2): 20 g, (p3): 30 g, (p4): 40 g, (p5): 50 g and five replications, so there are 25 units of treatment. Number of samples each treatment that is 4 plants. The observed variables in this study are plant height (cm), number of leaves per clump (split unit), number of chickens per spruce (fruit), fresh weight of tuber per hill (g) and dry weight of tuber wind clump (g). The results showed that the giving of Organic Solid Fertilizer had no significant effect on all observation variable. Keyword: Sabrang onion, Peat, Solid Organic Fertilizer.